Hydrogen storage properties in rapidly solidified TiZrVCrNi high-entropy alloys - Kumar A.; Yadav T.P.; Shaz M.A.; Mukhopadhyay N.K. (My University, 2025)
The development of alloys with substantial hydrogen storage capacities is a potential solution to the demand for hydrogen storage in a future hydrogen-based energy system. The synthesis, structural-microstructural properties, and hydrogen storage performance of a multicomponent TiZrVCrNi high-entropy melt-spun ribbon have been discussed in the present investigation. The x-ray diffraction and transmission electron microscopy investigations confirm that this as-cast and melt-spun alloy contains only a single C14-type hexagonal (a = b = 5.02 Å, c = 8.15 Å, α = β = 90°, γ = 120°) Laves phase. The room temperature pressure composition isotherms were studied with a pressure range of 0 to 40 atm. Continuing from our previous study in which we reported a hydrogen storage capacity of ~1.5 wt% in an as-cast high-entropy alloy synthesized using Arc melting, the total hydrogen storage capacity of TiZrVCrNi high-entropy melt-spun ribbons was found to be ~2 wt% in this work. This study makes the way forward for greater hydrogen storage in melt-spun ribbons. The observation of only minimal losses in storage capacity, even after 10 cycles of experiments on hydrogen absorption, shows that the reversible hydrogen storage capacity has high durability. To the best of our knowledge, these demonstrations are the first to present a study on the hydrogen storage capacity (~2 wt%) of the equiatomic TiZrVCrNi melt-spun ribbons. © 2023 John Wiley & Sons Ltd.